2003
DOI: 10.1143/jpsj.72.873
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Magnetic Properties of R1-xAxCoO3(R = La, Pr and Nd; A = Ba, Sr and Ca)

Abstract: Transport and magnetic measurements have been carried out on perovskite Co-oxides R 1-x A x CoO 3 (R=La, Pr, and Nd; A=Ba, Sr and Ca; 0≤x≤0.5: All sets of the R and A species except No indication of this kind of transition has been observed in other species of R.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 23 publications
3
58
0
Order By: Relevance
“…[14][15][16][17][18][19] Besides, our measurements show that above 100 K, an applied field of 9 T scarcely affects the resistivity and, in fact, slightly enlarges with the field. This demonstrates that the mobility of itinerant electrons does not depend on the magnetic arrangement of the core spins ͑t 2g 5 ͒.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…[14][15][16][17][18][19] Besides, our measurements show that above 100 K, an applied field of 9 T scarcely affects the resistivity and, in fact, slightly enlarges with the field. This demonstrates that the mobility of itinerant electrons does not depend on the magnetic arrangement of the core spins ͑t 2g 5 ͒.…”
Section: Discussionmentioning
confidence: 55%
“…For the nearest lanthanides to Pr, R =La ͑bigger͒ or Nd ͑smaller͒, this transition does not take place. 15 Taking this fact into account, the sudden shortening of the A-O bond distance coinciding with the enhancement of the resistivity must be interpreted in terms of the occurrence of electronic changes in Pr ions. This shortening could be due to a hybridization of Pr 4f and O 2p orbitals as reported for PrBa 2 Cu 3 O 7−␦ .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that pressure might have an influence on a spin-state transition at 100 K in LaCoO 3 [5]. Masuda et al have found resistivity anomaly at low temperature under pressure in Pr 0.7 Ca 0.3 CoO 3 which indicated the existence of the phase transition [6]. In Ref.…”
Section: Introductionmentioning
confidence: 96%
“…[5][6][7][8] For the combinations of large Ba 2+ ions and relatively small R 3+ ions, the system forms several kinds of the oxygen-deficient perovskite structure, in which the oxygen vacancies are ordered, [9][10][11][12][13][14][15][16][17] and a various physical behaviors are expected. However, only the restricted information is available on both the structural properties and the electronic properties.…”
Section: Introductionmentioning
confidence: 99%